2015
DOI: 10.1177/0003489415601687
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural and Moroccan Validation of the University of Washington Quality of Life Questionnaire for Patients With Head and Neck Cancer

Abstract: The Moroccan UW-QOL questionnaire appears to be culturally appropriate and psychometrically valid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
2
1
0
Order By: Relevance
“…Similar results were noted by other studies (Lee et al, 2017;Linardoutsos et al, 2014;Nazar et al, 2013;Şenkal et al, 2012). The overall mean score observed in the study was lower than that observed in other studies (Adnane et al, 2016;Jose Guilherme Vartanian et al, 2006;Lee et al, 2017;Linardoutsos et al, 2014;Nazar et al, 2013;Sakthivel et al, 2017;Şenkal et al, 2012). The subjects were interviewed before initiation of treatment.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were noted by other studies (Lee et al, 2017;Linardoutsos et al, 2014;Nazar et al, 2013;Şenkal et al, 2012). The overall mean score observed in the study was lower than that observed in other studies (Adnane et al, 2016;Jose Guilherme Vartanian et al, 2006;Lee et al, 2017;Linardoutsos et al, 2014;Nazar et al, 2013;Sakthivel et al, 2017;Şenkal et al, 2012). The subjects were interviewed before initiation of treatment.…”
Section: Discussionsupporting
confidence: 85%
“…16 Internal consistency of the translated questionnaire was high with a Cronbach's alpha coefficient of 0.88. This is comparable with other UW-QOL version 4 translations in other languages such as Spanish (0.84) 21 , Brazilian Portugese (0.744) 22 , Turkish (0.757) 23 , Moroccan Arabic (0.829) 24 , Greek (0.83) 25 , and Chinese (0.88) 26 .…”
Section: Discussionsupporting
confidence: 81%
“…Understandably, symptoms felt before and after the operation would change substantially resulting in a great fluctuation between the consistency of the test scores, and yielding a high p value of Pearson's correlation coefficient and a low test-retest reliability score. Other translations [21][22][23][24][25][26] of the questionnaire showed better test-retest reliability scores because no treatment was done in the two-week interim between the tests.…”
Section: Discussionmentioning
confidence: 99%